The Role of β-Glucan Particles in Driving Type I Interferon Induced Trained Immunity - Horneck Johnston, Cian (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2026)
Effective antiviral immunity requires rapid early pathogen control while maintaining a balanced inflammatory response. Trained immunity, whereby innate immune cells develop enhanced secondary responses through sustained metabolic and epigenetic reprogramming, represents a potential strategy to improve host resilience. While fungal β-glucans are well established in antibacterial and antitumour contexts, their role in antiviral defence, particularly following dietary delivery, remains unclear. In this thesis, I investigated whether yeast-derived β-glucan can induce antiviral trained immunity and defined the underlying mechanisms. Using Saccharomyces cerevisiae-derived whole glucan particles (WGP), I demonstrate that WGP induced durable metabolic reprogramming alongside stable epigenetic modifications. These effects required Dectin-1 engagement and phagocytosis. Following stimulation with viral ligands or live viral infection in vitro, trained cells mounted amplified type I interferon (IFN-I) and interferon-stimulated gene responses, resulting in improved viral control. Mechanistically, β-glucan training inhibited fumarate hydratase (FH), a tricarboxylic acid cycle enzyme that regulates antiviral immunity. FH inhibition promoted mitochondrial nucleic acid release, triggering IFN-I signalling and priming macrophages into an antiviral state. To establish in vivo relevance, mice were orally supplemented with WGP for up to four weeks. Dietary β-glucan induced central and peripheral features of trained immunity, including expansion of bone marrow progenitors, epigenetic reprogramming of circulating monocytes, and remodelling of lung alveolar macrophages. These effects were IFN-I dependent and persisted following β-glucan withdrawal, as demonstrated by enhanced responses to intranasal poly(I:C) challenge. In summary, this thesis identifies a previously unrecognised mechanism of β-glucan-induced antiviral trained immunity, termed Interferon-Dependent immune Training (IDT), providing a framework for exploiting dietary fungal components to enhance host preparedness against emerging viral infections.
APPROVED
Keywords: Trained immunity; Beta Glucan; Viral Immunology; Macrophage